Effect of a biomechanical factor on energy expenditure by distance runners during repeated vertical jumps - Seki, K.; Numazu, N.; Ohyama Byun, K.; Enomoto, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
This study aimed to clarify a biomechanical factor that would affect energy expenditure during repeated vertical jumps. The subjects, nine male Japanese distance runners, jumped for 3-min periods on a force platform under four different conditions. Motion and electromyography (EMG) data were recorded with a high-speed camera and surface electrodes, respectively. The following results were obtained: 1) the integrated EMG of the rectus femoris and vastus lateralis was greater in the Low and Decline conditions than in the High and Incline conditions, and 2) mechanical work at the ankle was greater in the High and Incline conditions than in the Low and Decline conditions. Thus, increased knee extensor muscular activity may increase the energy expenditure, and the stretch-shortening contraction of the gastrocnemius muscle may be more efficient.